PROBLEMATIKA LEMBAGA KEUANGAN MIKRO SYARIAH: STUDI PADA KOPSYAH BMT DI KOTA PALU - Wanita, Nur; Sofyan, Syaakir (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
This research is motivated by the existence of Islamic microfinance institutions in Palu City. In general, Islamic microfinance institutions named Islamic Cooperatives or Finance House (BMT) has enormous potential to empower community economy, particularly from the lower middle class. Since this institution is not only to raise funds, it also can channel it to meet people’s needs especially institutions’ member as well as for the communities’ in general. As time goes by, there is only one unit out of several units of Islamic Cooperatives or BMT in Palu that is still actively carrying out its operational activities, while the rest are already inactive. Therefore, this study tries to raise the issue of how the problems faced by Islamic microfinance institutions (Kopsyah BMT) in the city of Palu.